GAMIFICATION OF SCIENCE LEARNING IN A HYBRID SETTING: A STUDY ON STUDENT MOTIVATION AND CONCEPTUAL UNDERSTANDING - Ella Green; Harrison Davis; Isabella Clark (Journal Neosantara Hybrid Learning, 2025)
The integration of gamification into hybrid science learning environments has gained increasing attention as educators seek innovative strategies to enhance student motivation and conceptual understanding. The transition to hybrid models, combining online and face-to-face instruction, often challenges students’ engagement and persistence, particularly in science subjects that require abstract reasoning and sustained focus. This study investigates the effects of gamification elements such as points, badges, leaderboards, and narrative challenges on student motivation and conceptual comprehension in hybrid science learning settings. The research aims to determine whether game-based learning mechanics can improve both intrinsic motivation and mastery of scientific concepts. A quasi-experimental design was implemented with two groups of secondary school students (N = 120) participating in a hybrid science course over eight weeks. The experimental group used a gamified learning platform, while the control group followed conventional instruction. Data were collected through pre- and post-tests assessing conceptual understanding, alongside a motivation inventory adapted from the Science Motivation Questionnaire II. Statistical analysis using paired-sample t-tests and ANOVA revealed that the gamified group exhibited significantly higher motivation scores (M = 4.32, SD = 0.41) and improved conceptual understanding (p < 0.05) compared to the control group. The findings indicate that gamification fosters engagement and deeper learning by transforming abstract scientific ideas into interactive, goal-oriented experiences. The study concludes that integrating gamified elements in hybrid learning not only enhances cognitive outcomes but also sustains learner motivation across modalities.